2018
DOI: 10.1186/s13023-018-0857-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome level analysis in Rett syndrome using human samples from different tissues

Abstract: The mechanisms of neuro-genetic disorders have been mostly investigated in the brain, however, for some pathologies, transcriptomic analysis in multiple tissues represent an opportunity and a challenge to understand the consequences of the genetic mutation. This is the case for Rett Syndrome (RTT): a neurodevelopmental disorder predominantly affecting females that is characterised by a loss of purposeful movements and language accompanied by gait abnormalities and hand stereotypies. Although the genetic aetiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 106 publications
1
31
0
Order By: Relevance
“…MECP2 was generally regarded as a repressor, however its role as genetic activator has also been confirmed (Chahrour et al, 2008). In previous studies, a loss of function in MECP2 due to a mutation has been found to influence a variety of pathways and biological processes, including pathways related to not only neuron development and function, but also to the immune system, transcription, and translation related processes (which were identified mainly by transcriptome analysis, Colantuoni et al, 2001; Bedogni et al, 2014; Ehrhart et al, 2018; Shovlin and Tropea, 2018). The affected pathways identified with our study closely match the results previously found by Ehrhart et al (2018), in which human brain tissue data of Rett syndrome patients (published by Deng et al, 2007) was analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MECP2 was generally regarded as a repressor, however its role as genetic activator has also been confirmed (Chahrour et al, 2008). In previous studies, a loss of function in MECP2 due to a mutation has been found to influence a variety of pathways and biological processes, including pathways related to not only neuron development and function, but also to the immune system, transcription, and translation related processes (which were identified mainly by transcriptome analysis, Colantuoni et al, 2001; Bedogni et al, 2014; Ehrhart et al, 2018; Shovlin and Tropea, 2018). The affected pathways identified with our study closely match the results previously found by Ehrhart et al (2018), in which human brain tissue data of Rett syndrome patients (published by Deng et al, 2007) was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, omics data analysis on the level of genome, transcriptome, or proteome saw an increase in importance, to analyse and understand the holistic impact of MECP2, respectively, the impact of an impaired MECP2. Shovlin and Tropea (2018) recently reviewed the available transcriptomics studies on Rett syndrome and came to the conclusion that the most researched impact of MECP2 dysfunction lies with dendritic connectivity and synapse maturation, mitochondrial dysfunction, and glial cell activity. Recent pathway analysis results of single and integrated studies identified changes in intracellular signaling, including EIF2 (eukaryotic translation initiation) signaling, cytoskeleton, and cell metabolism including mitochondrial function (Bedogni et al, 2014; Ehrhart et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This then raises the question as to whether we can learn anything new from previously conducted studies through comparing existing data sets and ultimately extracting valuable information by conducting meta‐analysis. A notable example of utilizing omic data within the Rett syndrome research field is the recent study by Shovlin and Tropea () that delineated transcriptomic data from human Rett syndrome patient samples, to present trends in differential gene expression for investigating broader research questions.…”
Section: Introductionmentioning
confidence: 99%
“…Conditionally ablating MECP2 from the mouse brain recapitulates several findings in patients with Rett Syndrome, such as uncoordinated gait and repetitive movements 37,38 . Gene expression profiling of mouse models as well as human brain tissue has revealed widespread changes in gene expression across brain regions [39][40][41] , consistent with MECP2's role in modulating chromatin topology.…”
Section: Chromatin-associated Proteinsmentioning
confidence: 69%